Analisis Efektivitas Organisasi dengan Pendekatan Model 7S Mckinsey (Studi Pada Bank Syariah Indonesia Medan) - Sari Siregar, Salwa Nurmala; Marpaung, Nicholas; Siregar, Onan Marakali (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Organizational change is an important issue in a company, change provides an opportunity for the organization to improve performance from the previous one. As a merged company, Bank Syariah has made many changes. After the merger process carried out by several Islamic banks such as Bank BRI Syariah, Bank BNI Syariah, and Bank Mandiri Syariah, it is necessary to review whether the banking company's business operations are effective or not. This study was conducted to analyze how effective the Bank Syariah Indonesia company is after the merger using the McKinsey 7S model approach. And to find out the obstacles experienced by Bank Syariah Indonesia after the merger The form of research used by researchers in this study is qualitative with a descriptive approach. Data collection techniques are carried out by field studies with interviews and observations. Based on the analysis conducted, it was found that BSI Medan showed ineffective organizational effectiveness. Although several elements such as staff and skills, strategy, system, structure, and style showed a fairly good level of effectiveness, the main obstacle lies in the unification of organizational culture in the shared value element. The main obstacle detected was changes in organizational culture. In addition to obstacles in organizational culture, obstacles that occurred in BSI were in the form of technology adaptation, communication between employees, alignment of SOPs and services, and obstacles in increasing assets and customer growth. Currently, the company needs to continue to strengthen and align elements of the 7S model, help employees adapt to the new culture, and conduct regular evaluations of the implementation of the McKinsey 7S model.